Skowroński Krzysztof Piotr & Sami Pihlström (eds), Pragmatist Kant: Pragmatism, Kant, and Kantianism in the Twenty-first Century - Kemling, Jared (European Journal of Pragmatism and American Philosophy, 2019)
Pragmatist Kant: Pragmatism, Kant, and Kantianism in the Twenty-first Century is a collected volume featuring chapters from seventeen different authors. As the title indicates, the goal of the volume is to explore the relationship between the Kantian and pragmatist philosophical traditions – in both their historical and contemporary configurations. The editors note that “The papers collected in this volume were originally presented at the international conference, Pragmatist Kant, organized b.